(3CfehPL GdbJGd aj fbd GdYhGds - (3GHf CHj MLdI , CMeO Hf jMji Hf CHj HcQ GdJdeSGfj, TgGH GdOjf CHh GdYHGS,J (B776 (3g` s
(3ChdgG (B:s
(3CeG HYO adeG cGf GdTWQfL eeG CbGe Ydi eUfag GdOdjd hCUHM GddGYH Hg ai eUQ eG jacQ ai Gdajd EP gh eeGJYGWGg Gdedhc hGdCcGHQ s
(3BNQgG (B:s
(3hfSCd Gddg ZaQGf PfhHfG cdgG jhe JCJi cd faS JLGOd Yf faSgG Efg LhGO cQje QDha QMje s
(3GdfSNI HgG MhGTs
(3HBNQg bGFeI HGdcJH GdJi HMKJ Yf GdTWQfLs
(3fSNI KGfjI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B268s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B136s
Keywords: (3GdTWQfLs